Circular Bioeconomy Pathways for High-Value Agricultural Waste Valorization: A Systematic Review - Veronika Sriwulantari; Amri Syahardi; Delni Alek Candra; Heri Faisal Harahap; Veronice Veronice (Journal of Agriculture, 2026)
Agricultural intensification has increased the volume of residues and by-products generated across farming systems, while conventional disposal practices continue to create environmental burdens. This systematic literature review examines how agricultural waste is converted into higher-value products within a circular bioeconomy framework. Using a PRISMA-based approach and Scopus as the main database, the review screened the literature and synthesized 10 studies that met the final eligibility criteria. The included studies were grouped into four valorization pathways: fuels and energy carriers, biocomposites and bio-based materials, catalysts and functional carbon materials, and biomaterials produced through biotechnological processes. The evidence shows that fuel-oriented pathways, including pelletization, co-combustion, and biogas-based utilization, are the most technologically mature and currently offer the clearest route to scale. Material-based pathways, especially biocomposites and paper substitution, offer greater value addition and resource efficiency, but their industrial expansion remains constrained by processing costs and system integration. Agricultural residues also show strong potential as precursors for catalysts and functional carbon materials for environmental remediation, while fungal bioconversion offers an emerging route for producing protein-rich biomass. Across pathways, the review identifies a recurring trade-off between technological maturity, value addition, and implementation complexity. The main contribution of this review is a cross-pathway synthesis that compares agricultural waste valorization not only by product type, but also by circularity features, readiness, and evidence strength. Future research should prioritize integrated techno-economic assessment, life-cycle assessment, standardized circularity metrics, and pilot-scale validation to support large-scale implementation.